2001
DOI: 10.1038/sj.bjp.0703944
|View full text |Cite
|
Sign up to set email alerts
|

Inducible nitric oxide synthase (iNOS) activity promotes ischaemic skin flap survival

Abstract: 1 We have examined the role of nitric oxide (NO) in a model of functional angiogenesis in which survival of a skin¯ap depends entirely on angiogenesis to provide an arterial blood supply to maintain tissue viability. 2 The dierent eects of nitric oxide synthase (NOS) inhibitors on rat skin¯ap survival appeared to be explained on the basis of their NOS isoform selectivity. Skin¯ap survival was decreased by iNOS-selective (inducible NOS) inhibitors, S-methyl-isothiourea, aminoguanidine and aminoethylthiorea; una… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 32 publications
4
44
0
2
Order By: Relevance
“…Increased tissue survival resulting from iNOS-dependent enhancement of VEGF levels and an ensuing angiogenic response has been reported (23). These findings suggest that the SIS-ADSC grafts may contribute to tissue restoration by enhancing angiogenesis directly or indirectly.…”
Section: Discussionmentioning
confidence: 54%
“…Increased tissue survival resulting from iNOS-dependent enhancement of VEGF levels and an ensuing angiogenic response has been reported (23). These findings suggest that the SIS-ADSC grafts may contribute to tissue restoration by enhancing angiogenesis directly or indirectly.…”
Section: Discussionmentioning
confidence: 54%
“…11 The present study could explain this phenomenon because we now show that erythrophagocytosis, similar to platelet phagocytosis, 12 stimulates iNOS expression and because iron is known to promote lipid peroxidation 25 and ceroid formation. 8 The function of iNOS expression is not clear, but possible roles in atherogenesis and thrombus vascularization have to be considered because plaque progression 29 and angiogenesis during wound healing 30 are reduced in iNOS-deficient mice.…”
Section: Kockx Et Al Inos-expressing Macrophages and Microhemorrhagesmentioning
confidence: 99%
“…A second difference from previous experiments is that we used mice treated with iNOS inhibitor in the acute stage, as well as iNOS knockout mice, to examine the effect of iNOS [44]. It is noteworthy that one study in which iNOS knockout mice were used and reperfusion was not performed (similar to our protocol) found that injury was severe and angiogenesis in the chronic stage was augmented [45].…”
Section: Discussionmentioning
confidence: 99%
“…Many reports indicate that iNOS enhances angiogenesis in various neoplastic disease models [44,[47][48][49]. However, factors secreted by the cancer cells may play important roles in these models.…”
Section: Discussionmentioning
confidence: 99%